Effects of HSP70 on TLR4 Expression by Increasing MAPK and NF-KB Signaling Pathways in Periodontitis - Siamak Sandoghchian Shotorbani; adel espotin; javad mahmoudi; amir dehghan; saeed sadigh eteghad (Mashhad University of Medical Sciences, 2021)
Introduction: According to previous studies, heat shock protein 70 (HSP70) plays a role in the production of proinflammatory cytokines and inflammation. Given that no study has been performed in the field of dentistry in this regard, the present research aimed to identify the effect of HSP70 on moderate to severe generalized chronic periodontitis with the increase of mitogen-activated protein kinase (MAPK) and toll-like receptor 4 (TLR4) signaling pathways. Materials and Methods: This pilot study was performed on 50 subjects with moderate to severe chronic generalized periodontitis and 50 subjects with healthy periodontitis who were candidates for crown lengthening (CL) surgery. The subjects were selected based on the inclusion criteria from the patients who referred to the Gingival Surgery Department in a Private Dental Center, Tabriz, Iran. Tissue samples were obtained from the patients during pocket depth reduction surgery (for the experimental group) and CL surgery (for the control group). Macrophage inflammatory cells were extracted from tissue samples and the cells were stimulated by HSP70 as a timer; subsequently, the level of TLR4 in macrophage cells was examined. Results of the study were reported using descriptive statistical methods, such as mean, standard deviation, and frequency percentage. Repeated measures analysis was used to compare the expression of TLR4 in nuclear factor kappa B (NF-KB) and MAPK pathways at different hours. Moreover, ANOVA analysis of covariance was used to compare this rate between these two pathways at different times. Statistical analysis was performed in SPSS software (version 17) and a p < /em>-value of Results: Based on the results, there was a significant relationship between TLR4 and HSP70 (p < /em><0.001). Furthermore, in the tissue with chronic periodontitis, there was a significant relationship between the affected tissue and TLR4 (p < /em><0.0001). It was also found that TLR4, MAPK, and NF-KB levels increased in the presence of HSP70. Conclusion: According to the findings, it can be said that TLR4 expression levels increased in the presence of HSP70 in periodontitis and can increase even more by excitation of MAPK and NF-KB pathways.